Influence of Motivation and Competence on Employee Performance at Bank BJB Sumedang Branch - Adilla Shabarina; Ipa Hafsiah Yakin (SINTESA, 2023)
The core problem in this study is to determine the effect of motivation and competence on employee performance at Bank BJB Sumedang Branch. The method used in this research is quantitative research method, the number of respondents is 60 people, data collection techniques with questionnaires and data analysis techniques using path analysis. The results of the study prove that the effect of motivation on employee performance is 0.760 or 76.0% with Sig 0.000, meaning that work motivation has a significant effect on employee performance. The effect of competence on employee performance is 0.305 or 30.5% with Sig 0.000, meaning that competence has a significant effect on employee performance at Bank BJB Sumedang Branch Office. The effect of motivation and competence on employee performance at Bank BJB Sumedang Branch Office is 0.926 or 92.6% with a coefficient of determination of 85.8%, meaning that the effect of motivation and competence on employee performance is 85.8% in the value range of 60% - 80% or has a strong influence while the remaining 14.2% is influenced by other factors not examined in this study. The results of the static calculation show that the calculated F value of 171.862 is greater than the F table of 3.16. To improve employee performance at Bank BJB Sumedang Branch Office through motivation and competence, Bank BJB should supervise and check all information, both complaints, information services and attention to clarity and certainty of human resource management policies in the banking sector at Bank BJB Sumedang Branch Office and reduce the uncertainty of policies that cannot be applied in human resource management management.